Towards a conceptual framework to manage BIM/COBie asset data using a standard project management methodology. Issue 2 (15th November 2018) - Alnaggar, Ahmed; Pitt, Michael
Abstract : Purpose: The purpose of this paper is to investigate a systematic methodology to manage asset data flow between building stakeholders throughout building life cycle using the Construction Operation Building Information Exchange (COBie) standard. Design/methodology/approach: A literature review of the relevant building information modelling (BIM) for facilities management (FM) studies including the gaps and challenges of producing COBie data is analysed. Then a standard project management methodology by Project Management Institute (PMI) is introduced as a theoretical framework to map the different areas of managing COBie data as a project in coordination with Royal Institute of British Architects (RIBA) Plan of work. This theoretical background is coupled with an inductive approach through the placement within a construction company (Bouygues, UK) in the UCLH construction project to produce the conceptual framework that is aligned with industry needs. Findings: The lack of well-structured approach to manage COBie data throughout building life cycle causes many problems and confusions about the roles and responsibilities of different stakeholders in creating and managing asset data. This confusion in turn results in incomplete and low-quality COBie data at the handover phase which hinders the ability of facility managers to use these data effectively in the operations phase. The proposed conceptual framework provides a standard project management process to systemise the data flow among all stakeholders. Practical implications: The proposed framework is developed in liaison with a large construction company, so it is well aligned with an actual industry approach to managing COBie data. Furthermore, it provides a systematic step-by-step approach to managing COBie as a project that could be easily implemented in actual construction projects. Originality/value: The paper introduced a novel approach to manage COBie data using a standard project management methodology based on an actual live construction project perspective coupled with project management theory.